Public-Public Collaboration for Food Safety Risk Management: Essence, Modes, and Identification of Key Influencing Factors Using DANP - Zhang, Liwei; Qin, Ke; Li, Yufeng; Wu, Linhai (Frontiers in Public Health, 2022)
Objective Food safety risk management is an important cross-boundary issue from both theoretical and practical standpoints. Because food safety has the social attributes of public goods, public-public collaboration can be considered a particularly important mode of cross-boundary governance. The study aims to provide a theoretical basis for the Chinese government to promote public-public collaboration for food safety risk management by identifying key factors. Methods Based on a review of literature across diverse fields, such as political science, sociology, and new public governance, this study discusses the essence, modes, and dilemma of public-public collaboration for food safety risk management using practical explorations in various countries as the main thread and taking into account the actual situation in China. Moreover, this study quantitatively analyzes the relationships between the dimensions and factors affecting public-public collaboration and identifies key dimensions and factors using the Decision-making Trial and Evaluation Laboratory-based Analytic Network Process (DANP). Results Among the 20 factors in the calculation results of DANP, Lawmaking has the highest value of (fi+ei) (7.022) and ranks sixth in terms of influence weight. The (fi+ei)value of Professionalism (6.993) ranks second and its influence weight ranks fourth. The (fi+ei) value of Administrative enforcement (6.722) ranks fifth, and its influence weight ranks seventh. The (fi+ei) value of Improvement of the social environment (6.699) ranks sixth, and its influence weight ranks fifth. The (fi+ei) value of Legal authorization (6.614) ranks seventh, and its influence weight ranks tenth. Data analysis indicated that these are the five key factors affecting the governance capacity in public-public collaboration for food safety risk management. Conclusion The legal basis is the most important dimension affecting public-public collaboration. Legislation-based governance, administrative law enforcement–based governance, and social environment improvement–based governance in the behavior and capabilities dimension, professionalism in the basic characteristics dimension, and laws and regulations in the legal basis dimension are the five key factors.